Teacher's Perception on The English We Speak Podcast as Learning Media - Adam Putro Kuncoro; Lidiyatul Izzah; Desi Purnama Kurniawati; Sri Iswarin (English Language in Focus (ELIF), 2022)
AbstractTechnology is an asset for mankind, a great invention that drives a civilization to be more advanced. Its use is very useful to support human desires and achievements in all aspects. Technology has played an important role without exception, of course we can have a good or bad impact depending on the use of this technology in our lives. In the field of education, the use of technology is an opportunity to advance and rejuvenate children in learning. This study aims to enable teachers or teaching staff out there to consider podcasts as an introductory medium for listening material in English. In this study using descriptive qualitative methods to find the data needed also to find out whether this media has a positive or negative impact on its implementation. This study uses the perceptions of teachers or teaching staff. The teacher is one of the agents of the learning material, of course the teacher will understand better whether a media has a good impact or not in the learning development of their students.Keywords: podcast, audio digital, learning media.